Analysis of Leadership Style, Workload, and Work Culture on Company Performance, With Work-Life Harmony as a Moderator. A Case Study of PT PLN UP3 Banyuwangi - Nur Rella Catur Trisno Wahyudi; Sri Gunani Partiwi (Green Publisher Indonesia, 2026)
Organizations need to adapt proactively in the face of technological disruption and global uncertainty to sustain organizational performance. Human resource management has therefore become a key strategy, not only to achieve performance targets but also to maintain employee well-being and harmony between work and personal life. This study aims to examine the determinants of company performance by analyzing leadership style, workload, and work culture, with work-life harmony as a moderating variable, while also formulating evidence-based recommendations for human resource management policies. The study was conducted at PT PLN (Persero) UP3 Banyuwangi, which is characterized by a multigenerational workforce and high-performance targets. A quantitative approach was applied using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method through SmartPLS software. Data were collected from 84 employees using a digitally distributed Likert-scale questionnaire. The results indicate that leadership style, workload, and work culture do not have a significant direct effect on company performance. In contrast, work-life harmony has a positive and significant effect on performance (β = 0.825; p < 0.001). Furthermore, work-life harmony significantly moderates the relationship between leadership style and company performance (β = 0.233; p = 0.002), as well as the relationship between work culture and performance in a negative direction (β = −0.184; p = 0.021), while it does not significantly moderate the relationship between workload and performance.